Candid science four - Hargittai, Magdolna (Imperial College Press, 2004)
Includes indexes.; Eugene P. Wigner -- Steven Weinberg -- Yuval Ne'eman -- Jerome I. Friedman -- Martinus J.G. Veltman -- Gerard 't Hooft -- Leon M. Lederman -- Valentine L. Telegdi -- Val L. Fitch -- Maurice Goldhaber -- John N. Bahcall -- Rudolf Mèossbauer -- Arno A. Penzias -- Robert W. Wilson -- Owen Chamberlain -- Marcus L.E. Oliphant -- Norman F. Ramsey -- David E. Pritchard -- Wolfgang Ketterle -- Laszlo Tisza -- Edward Teller -- John A. Wheeler -- Freeman J. Dyson -- John C. Polkinghorne -- Benoit B. Mandelbrot -- Kenneth G. Wilson -- Mildred S. Dresselhaus -- Catherine Brâechignac -- Philip W. Anderson -- Zhores I. Alferov -- Daniel C. Tsui -- Antony Hewish -- Jocelyn Bell Burnell -- Joseph H. Taylor -- Russell A. Hulse -- David Shoenberg.